The wild robot escapes - Brown, Peter, 1979-; Brown, Peter, 1979- (New York : Little, Brown and Company, 2018)
After being captured by the Recons and returned to civilization for reprogramming, Roz is sent to Hilltop Farm where she befriends her owner's family and animals, but pines for her son, Brightbill.
Sequel to: The wild robot.
School Library Journal starred, March 2018
Booklist starred, January 2018
Bulletin (Center for Children's books), March 2018
Kirkus Review, February 2018
5.0
Keywords: Robots -- Fiction; Farm life -- Fiction; Domestic animals -- Fiction; Action and adventure fiction; Science fiction